Glucose‐6‐phosphate dehydrogenase (G6PD)‐deficient infants: Enzyme activity and gene variants as risk factors for phototherapy in the first week of life. (4th April 2017) - Wong, Fei‐Liang; Ithnin, Azlin; Othman, Ainoon; Cheah, Fook‐Choe
Abstract : Aim: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is a recognised cause of severe neonatal hyperbilirubinaemia, and identifying which infants are at risk could optimise care and resources. In this study, we determined if G6PD enzyme activity (EA) and certain gene variants were associated with neonatal hyperbilirubinaemia requiring phototherapy during the first week after birth. Methods: Newborn infants with G6PD deficiency and a group with normal results obtained by the fluorescent spot test were selected for analyses of G6PD EA and the 10 commonly encountered G6PD mutations in this region, relating these with whether the infants required phototherapy before discharge from the hospital in the first week. Results: A total of 222 infants with mean gestation and birth weight of 38.3 ± 1.8 weeks and 3.02 ± 0.48 kg, respectively, were enrolled. Of these, n  = 121 were deficient with EA ≤6.76 U/g Hb, and approximately half (43%) received phototherapy in the first week after birth. The mean EA level was 3.7 U/g Hb. The EA had good accuracy in predicting phototherapy use, with area under the receiver‐operating‐characteristic curve of 0.81 ± 0.05. Infants on phototherapy more commonly displayed World Health Organization Class II mutations (<10% residual EA). Logistic regression analysis showed that deficiency in EA and mutation at c.1388G>A (adjusted odds ratio, 1.5 and 5.7; 95% confidence interval: 1.31–1.76 and 1.30–25.0, respectively) were independent risk factors for phototherapy. Conclusion: Low G6PD EA (<6.76 U/g Hb) and the G6PD gene variant, c.1388G>A, are risk factors for the need of phototherapy in newborn infants during the first week after birth.